The Empowerment enhancement: A significant predictor of Chinese lecturers’ self efficacy and Job performance - Wei Guorong,; Hanim Yusuf, Asindar (Technium Social Sciences Journal, 2020)
The aim of the study was to estimate the impact of empowerment enhancement on lecturers’ job performance and self efficacy. Further to this the mediating role investigation was also the purpose of this study. In order to complete the research 375 observations were collected from lecturers working in Chinese university in Shanxi province. Structured self administered questionnaire was used for data collection. A number of statistical techniques were used for analysis purpose which yielded results. Based on collected results all developed hypothesis were accepted. Which showed that the results are matching with earlier conducted studies both in academic and corporate environment? Significance of empowerment enhancement as practical in corporate sector as in academic settings.